The Practices of Stereotyping of Black Women Scientist in Film Hidden Figures - Sri Amalia Tompunu; Magdalena Baga; Novi Rusnarty Usu (Transbahasa, 2025)
This study explores the stereotyping practices faced by Black women in the film Hidden Figures (2016), focusing on the lived experiences of three central characters—Katherine Johnson, Dorothy Vaughan, and Mary Jackson. Using feminist literary criticism and the